1992
DOI: 10.1203/00006450-199202000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varying Arterial Oxygen Tension on Neonatal Acid-Base Balance

Abstract: ABSTRACT. Acute severe hypoxia, when the arterial partial pressure of O2 (Pao2) is sufficiently reduced, causes a shift from aerobic to anaerobic metabolism and can be fatal to neonates. The ability of the neonate to accommodate this shift, and prevent acidosis, could play a role in its ability to tolerate hypoxia. This study examines the effect of varying degrees of acute hypoxia on acid-base homeostasis in the neonate using a model of right to left shunting where Pa02 is decreased and, if severe, arterial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Goldstein et al (1995) found metabolic acidosis to be the best biochemical predictor of outcome at the age of 24 months. In the current study, initial arterial pH, but not initial base excess (an indicator of metabolic acid-base status of the buffering system independent of respiratory acidosis or alkalosis; Golderger, 1986;Goldstein et al, 1995;Torrance & Wittnich, 1992) accounted for a larger proportion of outcome variance. The differential statistical effect of the two risk indexes on outcome may, in part, stem from the fact that the standard deviation of the base excess was large relative to the mean, whereas the standard deviation of pH was comparatively small (in our total sample, initial base excess ± SD = -6.47 ± 3.56 milliequivalent per liter (mEq/L) vs. initial pH = 7.23 ± 0.05, with coefficients of variation of .55 and .01, respectively).…”
Section: Discussionmentioning
confidence: 46%
“…Goldstein et al (1995) found metabolic acidosis to be the best biochemical predictor of outcome at the age of 24 months. In the current study, initial arterial pH, but not initial base excess (an indicator of metabolic acid-base status of the buffering system independent of respiratory acidosis or alkalosis; Golderger, 1986;Goldstein et al, 1995;Torrance & Wittnich, 1992) accounted for a larger proportion of outcome variance. The differential statistical effect of the two risk indexes on outcome may, in part, stem from the fact that the standard deviation of the base excess was large relative to the mean, whereas the standard deviation of pH was comparatively small (in our total sample, initial base excess ± SD = -6.47 ± 3.56 milliequivalent per liter (mEq/L) vs. initial pH = 7.23 ± 0.05, with coefficients of variation of .55 and .01, respectively).…”
Section: Discussionmentioning
confidence: 46%